Mathematics
richardmercer01
2015-10-31 08:22:00
How do I solve please explain 4x^5y^-3
ANSWERS
taylung
2015-10-31 12:30:34

4x - 5y = -3  ⇒ 1st equation 2x + 3z = 4  ⇒ 2nd equation 3y - z = 8     ⇒ 3rd equation find the value of z. 3y - z = 8 - z = 8 - 3y z = (8 - 3y) / -1 z = -8 + 3y Substitute z with its value in the 2nd equation: 2x + 3z = 4 2x + 3(-8 + 3y) = 4 2x - 24 + 9y = 4 2x + 9y = 4 + 24 2x + 9y = 28 find value of x 2x + 9y = 28 2x = 28 - 9y x = (28 - 9y)/2 x = 14 - 9y/2 Substitute the value of x in 1st equation 4x - 5y = -3 4(14-9y/2) - 5y = -3 56 - 36y/2 - 5y = -3 - 36y/2 - 5y = -3 - 56 - 36y/2 - 5y = - 59 2(-36y/2 - 5y) = 2(-59) -36y - 10y = -118 -46y = -118 -46y/-46 = -118/-46 y = 2 26/46 y = 2 13/23   x = 14 - 9y/2 x = 14 - 9 (2 13/23) /2 x = 14 - 9 (59/23) / 2 x = 14 - 531/23 / 2 x = 14 - 531/23 * 1/2 x = 14 - 531/23*2 x = 14 - 531/46 x = (14*46/46) - 531/46 x = 644/46 - 531/46 x = (644-531)/46 x = 113/46 x = 2 21/46 z = -8 + 3y z = -8 + 3(2 13/23) z = -8 + 3(59/23) z = -8 + 177/23 z = (-8*23/23) + 177/23 z = -184/23 + 177/23 z = (-184 + 177)/23 z = -7/23 x = 2 21/46 ; y = 2 13/23 ; z = -7/23 4x - 5y = -3 4(113/46) - 5(59/23) = -3 452/46 - 295/23 = -3 9.826 - 12.826 = -3 -3 = -3 2x + 3z = 4 2(113/46) + 3(-7/23) = 4 226/46 - 21/23 = 4 4.913 - 0.913 = 4 4 = 4 3y - z = 8 3(59/23) - (-7/23) = 8 177/23 + 7/23 = 8 7.696 + 0.304 = 8 8 = 8 

ADD ANSWER